ЎРТА СИНФ – БОЗОР ИҚТИСОДИЁТИНИНГ ЕТАКЧИ КУЧИ (Scientific journal of the Fergana State University, 2023)
In this article is proved the importance of the multilateral operational organization of the middle class in the transition to a market economy.